The Role of Decision Makers in Late Maternal Referrals - Albertina Bata, Verayanti; Emilia, Ova; Hakimi, Mohammad (Poltekkes Kemenkes Kupang, 2019)
Background: Three delays models in referring the mother to health facility are the most important determinants in maternal mortality. Based on the culture in West Sumba, most of the people still follow patrilinear patrimony. This culture limiting women to make decisions such as the decision to determine where to get health services, plan the number of children and bird spacing. The first model should be immediately prevented from causing the next delay which is late in making a family decision and too late to recognize danger sign in pregnancy that affects maternal mortality. Purpose: The purpose of this study was to explore the role of decision-makers in delayed maternal referrals. Methods: Qualitative research using the phenomenological design on 5 mothers who experienced a delay in referral at Padediwatu Primary Health Care. Data collected with in-depth interviews. Result: Decision maker in maternal referring was dominated by the husband. Obstacles in the referral process such as not having a vehicle, long distances and difficult road access, low economic status, and the culture that depend on others so maternal health status with complications is not a priority for the husband. Husband's work as a farmer and sailor that keeps the husband away from home or near to his wife for long periods was affected by the decision-making process of maternal referral. Conclusion: Decision-making in maternal referrals still emphasizes patrilinierculture, husbands have an important role in making maternal referral decision.